Economic Value of Coastal Resources based on Ecotourism Activity in the Sanggar Beach, Tulungagung - Amalia Febryane Adhani Mazaya; Agrilina Pramesthi Dua; Pribadi Elrika Wafa Sabrina; Nurkhasanah Anissa Aprilia; Rini (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2026)
This study was conducted to calculate the economic value of coastal resources based on ecotourism activities at Sanggar Beach, Tulungagung, East Java, Indonesia. As a turtle nesting habitat and tourist destination, Sanggar Beach offers ecological and economic value. However, economic values such as non-market benefits are often overlooked in tourism assessments. In fact, economic assessment is one of the inputs for sustainable coastal tourism destination management. Therefore, a mixed approach was used with a decision tree model to describe tourist characteristics, the Travel Cost Method (TCM) to analyze tourism demand, Principal Component Analysis (PCA) to describe the relationship between demographics and tourism demand, and consumer surplus analysis to calculate economic value. Data were collected from 30 tourists selected purposively through a structured questionnaire. The results show that travel costs, age, education, and income are predictors of tourism demand with the age being a ignificant predictor. The decision tree model further showed that older visitors reported higher levels of satisfaction, while younger groups were more influenced by socioeconomic factors. PCA revealed that the first two components explained 73,9% of the total variance, simplifying the analysis of visitor characteristics. Consumer surplus was estimated at IDR 64.016 per visitor, with the economic value of tourism activities projected at around IDR 18,064,987,438.00 per year. These results indicate that the indirect benefits of conservation areas can be considered in supporting sustainable ecotourism strategies, such as determining entrance fees and area incentives.